SmartBridge a scalable bridge architecture. - Rodeheffer, Thomas L. (Computer communication review.)
As the number of hosts attached to a network increases beyond what can be connected by a single local area network (LAN), forwarding packets between hosts on different LANs becomes an issue. Two common solutions to the forwarding problem are IP routing and spanning tree bridging. IP routing scales well, but imposes the administrative burden of managing subnets and assigning addresses. Spanning tree bridging, in contrast, requires no administration, but often does not perform well in a large network, because too much traffic must detour toward the root of the spanning tree, wasting link bandwidth.